Las creaciones (redacciones) literarias mediante, un proceso creativo y ordenado de la enseñanza aprendizaje del área de lengua y literatura de los niños y niñas de quinto, sexto y séptimo grados del subnivel básica media de educación general básica de la escuela “Uruguay” de la parroquia Amaluza, cantón Espíndola, provincia de Loja, año lectivo 2013-2014 - Gaona Cordero, Gloria Cecilia (2014)
The research related to the topic : The creations (essays ) literary means , a creative and orderly learning teaching language arts area for children in fifth, sixth and seventh grades average basic sublevel basic general education school " Uruguay " of the parish Amaluza , canton Espindola, Loja province , it was proposed the knowledge and treatment of the methodologies used in the forms of writing , learning, language and literature . The methodology is qualitative in nature , since research corresponds to the descriptive . This required the use of methods such as : Scientific Method , Method Description , Analytical Method - Synthetic and Theoretical or Deductive , as well as techniques as: Structured Interview and Survey . The instruments applied were Structured Interview Guide and questionnaire that were applied to teachers and students , respectively . In each of the sequences, according to the schedule you had planned the development of the activities allowed to arrive at the systematization and analysis of results. In the research process involved the following human talents : one leading , 3 teachers and 74 students . After processing the information, the main conclusion was established as Teachers select texts to help students in newsrooms civic literary dates , demarcated the creativity of the students to investigate other empirical sources that enable them to enrich their vocabulary . Finally it is recommended to institutional authorities to promote teachers in strategies to help students in newsrooms civic literary dates , facilitating the creativity of students to investigate other empirical sources that enable them to enrich their vocabulary